Penerapan Pendekatan Realistic Mathematic Education untuk Meningkatkan Prestasi Belajar Matematika Siswa Kelas 1 SD Muhammadiyah 03 Unggulan - Yusnidar Siregar; Radhiyatul Fithri; Salman Salman (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Mathematics learning is considered difficult for students to understand. In this way, teachers try to improve student learning achievement, one of which is by implementing a realistic mathematical education approach. This research aims to determine the application and learning achievement of students by applying a realistic mathematical education approach. This research method uses a qualitative method with the type of Classroom Action Research (PTK), which consists of two cycles. The data collection techniques are through observation, interviews and documentation. The research results obtained were the application of a realistic mathematical education approach to cycle I teachers from 62.5% to 66.6% in the good category. In cycle II from 75% to 83.3%. As well as the application of a realistic mathematical education approach to cycle I students from 57.1% to 59.2% in the quite good category. Cycle II from 74.5% to 85.8%. Meanwhile, the results of student learning achievement in cycle I from 50% to 61.1% were said to be incomplete. Cycle II from a value of 72.2% to 89%. Thus, through the application of a realistic mathematical education approach, student learning achievement can be improved.